2019
DOI: 10.1186/s13048-019-0546-9
|View full text |Cite
|
Sign up to set email alerts
|

Anti-proliferative effects of mesenchymal stem cells (MSCs) derived from multiple sources on ovarian cancer cell lines: an in-vitro experimental study

Abstract: Mesenchymal stem cells (MSCs) have surfaced as ideal candidates for treatment of different therapeutically challenging diseases however their effect on cancer cells is not well determined. In this study, we investigated the effect of MSCs derived from human bone marrow (BM), adipose tissue (AT), and umbilical cord derived MSCs (UC-MSCs) on ovarian cancer. Measurements of ovarian tumor marker proteins were computed by ELISA. Proliferative, apoptosis and anti-inflammatory effects of the MSCs were measured by Flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 66 publications
2
34
0
1
Order By: Relevance
“…In an experiment on breast cancer, MSCs were demonstrated to suppress cancer cell growth and sensitize the cancer cells to radiotherapy through inhibiting the STAT3 signaling pathway ( 26 ). Moreover, MSCs and their conditioned media also have a major role in anti-proliferation of ovarian cancer cells and can be considered as a potential therapeutic tool in ovarian cancer ( 27 ).…”
Section: The Pro- and Antitumor Properties Of Mscsmentioning
confidence: 99%
“…In an experiment on breast cancer, MSCs were demonstrated to suppress cancer cell growth and sensitize the cancer cells to radiotherapy through inhibiting the STAT3 signaling pathway ( 26 ). Moreover, MSCs and their conditioned media also have a major role in anti-proliferation of ovarian cancer cells and can be considered as a potential therapeutic tool in ovarian cancer ( 27 ).…”
Section: The Pro- and Antitumor Properties Of Mscsmentioning
confidence: 99%
“…These results suggest that HATMSC2-MVs at a ratio of 100:1 induce mechanisms governing ovarian cancer cell death via both apoptosis and necrosis. Studies on the anti-cancer properties of the MSC secretome report that co-culture of MSCs of different tissue origin with ovarian cancer cell lines increases apoptosis with varying effects [21]. Interestingly, the percentage of apoptotic cells was higher when the supernatant derived from AT-MSCs was applied compared to the supernatants derived from BM-MSCs and UC-MSCs [21].…”
Section: Effect Of Hatmsc2-mvs On the Secretion Profile Of Ovarian Camentioning
confidence: 99%
“…In this regard, the cross-talk between mesenchymal and tumor cells has been shown to induce transcriptomic changes in the latter, characterized by the upregulation of genes involved in cell proliferation, migration and invasiveness that ultimately lead to the acquisition of a pro-metastatic phenotype [ 49 ]. On the other hand, Khalil and co-workers demonstrated that MSCs from different sources were capable to exert a pro-apoptotic effect in vitro on several OC lines, while decreasing tumor cell invasiveness and aggressiveness [ 52 ]. In our experimental model, by co-culturing A2780 with tumor-derived ML-Ddx4 + cells, we observed that the latter did not compromise OC cell viability, but preserved their proliferation rate, as confirmed by the transcriptomic variations that we observed in subsequent experimental steps.…”
Section: Discussionmentioning
confidence: 99%